Association of mitral annular velocity with myocardial ischemia assessed by single-photon emission computed tomography in patients with suspected coronary artery disease and preserved ejection fraction. Issue 3 (March 2016) - Kurisu, Satoshi; Iwasaki, Toshitaka; Ikenaga, Hiroki; Watanabe, Noriaki; Higaki, Tadanao; Shimonaga, Takashi; Ishibashi, Ken; Dohi, Yoshihiro; Hidaka, Takayuki; Fukuda, Yukihiro; Kihara, Yasuki
Abstract : Background: Left ventricular diastolic dysfunction is a sensitive and early sign of myocardial ischemia. We assessed whether mitral annular velocity reflected the severity of myocardial ischemia evaluated by single-photon emission computed tomography in patients with suspected coronary artery disease (CAD) and preserved ejection fraction. Methods and results: The study population consisted of 125 patients with suspected CAD who underwent both single-photon emission computed tomography and transthoracic echocardiography. There were 68 patients with no ischemia, 42 patients with mild ischemia, and 15 patients with severe ischemia. With increasing severity of myocardial ischemia, septal e' decreased. Compared with patients with no ischemia, septal e' was significantly lower even in patients with mild ischemia (6.6±1.4 vs. 6.1±1.4 cm/s, P <0.05). Septal E/e' (9.9±2.6 vs. 13.6±4.0, P <0.01) and lateral E/e' (7.7±2.3 vs. 10.3±3.6, P <0.01) were significantly higher finally in patients with severe ischemia. Multivariate logistic regression analyses showed that BMI [odds ratio (OR) 1.13, 95% confidence interval (CI) 1.01–1.29; P =0.03] and septal e' (OR 0.71, 95% CI 0.53–0.94; P =0.02) were independent predictors of any myocardial ischemia and that diabetes (OR 5.78, 95% CI 1.58–23.0; P =0.008) and septal E/e' (OR 1.38, 95% CI 1.13–1.76; P =0.001) were independent predictors of severe myocardial ischemia. Conclusion: Our data suggested that decreased e' was useful in detecting mild myocardial ischemia and increased E/e' was useful in detecting severe myocardial ischemia in patients with suspected CAD and preserved ejection fraction.